2022
DOI: 10.1002/ieam.4644
|View full text |Cite
|
Sign up to set email alerts
|

Application of autonomous sensor technology to estimate selenium exposure and a site‐specific selenium threshold in a Canadian boreal lake

Abstract: There is an increasing trend in the use of real-time sensor technology to remotely monitor aquatic ecosystems. Commercially available probes, however, are currently not able to measure aqueous selenium (Se) concentrations. Because of the well-described bioaccumulation potential and associated toxicity of Se in oviparous vertebrates, it is crucial to monitor Se concentrations at sites receiving continuous effluent Se input. This study aimed to estimate Se concentrations in a boreal lake (McClean Lake) downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The goal of this study was to assess Se bioaccumulation in two model benthic macroinvertebrates, H. azteca and C. dilutus, under known exposure duration conditions. Thereby, this study also aimed to clarify results from earlier eld studies in which arti cial substrates were used to sample BMI in a boreal lake (McClean Lake) downstream from a uranium milling and mining operations in northern Canada (Mendes et al 2022a(Mendes et al , 2022b(Mendes et al , 2023 in press). To address this goal, two Se bioaccumulation studies were conducted to investigate Se bioaccumulation in H. azteca and the potential effect of biological competition in co-exposure with C. dilutus.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The goal of this study was to assess Se bioaccumulation in two model benthic macroinvertebrates, H. azteca and C. dilutus, under known exposure duration conditions. Thereby, this study also aimed to clarify results from earlier eld studies in which arti cial substrates were used to sample BMI in a boreal lake (McClean Lake) downstream from a uranium milling and mining operations in northern Canada (Mendes et al 2022a(Mendes et al , 2022b(Mendes et al , 2023 in press). To address this goal, two Se bioaccumulation studies were conducted to investigate Se bioaccumulation in H. azteca and the potential effect of biological competition in co-exposure with C. dilutus.…”
Section: Introductionmentioning
confidence: 95%
“…The previous on-site studies showed that diluted e uent distribution in McClean Lake E.B. is heterogeneous (Mendes et al 2022a) and varies depending on a season (AREVA 2016a).…”
Section: Study Sitementioning
confidence: 99%
“…Before deployment at Lake Miwasin, a similar WSN methodology was tested in Canadian lakes to delineate effluent exposure downstream of a Uranium Mill region (Cupe-Flores et al, 2022) and to estimate selenium (Se) exposure using a site-specific threshold value (Peixoto Mendes et al, 2023). In Lake Miwasin, deployment spanned from September 18 th to October 10 th in 2020; and from June 21 st to October 16 th in 2021.…”
Section: Data Used In Ml: Pilot Scale Pit Lakementioning
confidence: 99%
“…Exposure characterization describes the magnitude and spatial and temporal patterns of exposure to stressors (e.g., contaminants) shown in the conceptual model. To this end, autonomous sensor technology has been adapted to estimate exposure levels from pollutants such as metals in lakes associated with adverse effects (Peixoto Mendes et al, 2023). Some of the advantages of this technology include their wireless, remote, ubiquity, and real-time capabilities (Randhawa et al, 2017), which can lead to data collection from remote or hazardous sites.…”
Section: Editorialmentioning
confidence: 99%
“…As the affordability and accuracy of commercial sensors increase, their deployment and application also increase in monitoring activities and site identification (Randhawa et al, 2017). For example, real‐time electrical conductivity data from autonomous sensors have been shown to be a good surrogate for total aqueous selenium levels in a Canadian boreal lake and for identifying key monitoring locations (Peixoto Mendes et al, 2023). Autonomous sensors can not only be deployed to measure water‐quality parameters, but also, they can generate exposure estimates of levels of contaminants on a case‐by‐case basis, as shown for metals in aquatic ecosystems.…”
Section: Figurementioning
confidence: 99%